Pés descalços: o processo de criação da obra “Cálice” na poética da dança moderna, da Cia. Auxiliadora Monteiro Dance Company - LIMA, Mayra Monteiro (2018)
This Course Completion Work had as objective to analyze the process of creation of the work Cálice, in the language of modern dance, of the Auxiliadora Monteiro Dance Company. It should be noted that, the techniques of Martha Graham and Lester Horton were inspiring for the process of choreographic creation of the work. To analyze the present research object, the following authors were adopted as main theoretical references: Salles (2013) and Ostrower (1978) to deal with the process of artistic creation; Neves (2009), Leal (2006) and Monteiro (2014) for the study of the poetics and expressivity in modern dance. The research is descriptive, with an analytical approach to the process of creation in dance. It stands out in the work Cálice, the soundtrack of Chico Buarque, whose musical composition cálice is reflection of the difficulties faced during the military dictatorship occurred in Brazil. The present study was developed based on the experiences of the researcher at the Dance Company Auxiliadora Monteiro Dance Company, as well as interviews with the dancers of Cia. As a result, an investigation is made of the process of creation in dance, in order to strengthen research in the area of modern dance, contributing to the history of dance in Belém do Pará.